Non-invasive coronary angiography with multislice spiral computed tomography: impact of heart rate. Issue 5 (1st November 2002) - Nieman, K; Rensing, B J; van Geuns, R-J M; Vos, J; Pattynama, P M T; Krestin, G P; Serruys, P W; de Feyter, P J
Abstract : Objective: To evaluate the impact of heart rate on the diagnostic accuracy of coronary angiography by multislice spiral computed tomography (MSCT). Design: Prospective observational study. Patients: 78 patients who underwent both conventional and MSCT coronary angiography for suspicion of de novo coronary artery disease (n=53) or recurrent coronary artery disease after percutaneous intervention (n=25). Setting: Tertiary referral centre. Methods: Intravenously contrast enhanced MSCT coronary angiography was done during a single breath hold, and ECG synchronised images were reconstructed retrospectively. All coronary segments of ≥ 2.0 mm without stents were evaluated by two investigators and compared with quantitative coronary angiography. Patients were classified according to the average heart rate (mean (SD)) into three equally sized groups: group 1, 55.8 (4.1) beats/min; group 2, 66.6 (2.8) beats/min; group 3, 81.7 (8.8) beats/min. Results: Image quality was sufficient for analysis in 78% of the coronary segments in patients in group 1, 73% in group 2, and 54% in group 3 (p < 0.01). The sensitivity and specificity for detecting significant stenoses (≥ 50% lumen reduction) in these assessable segments were: 97% (95% confidence interval (CI) 84% to 100%) and 96% in group 1; 74% (52% to 89%) and 94% in group 2; and 67% (33% to 90%) and 94% in group 3 (p < 0.05). Accounting for all segments of ≥ 2.0 mm, including lesions in non-assessable segments as false negatives, the sensitivity decreased to 82% (28/34 lesions, 95% CI 69% to 91%), 61% (14/23 lesions, 42% to 77%), and 32% (6/19 lesions, 15% to 50%), respectively (p < 0.01). Conclusions: MSCT allows reliable coronary angiography in patients with low heart rates.